2013
DOI: 10.3892/or.2013.2773
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression and subcellular localization of familial acute myelogenous leukemia-related factor

Abstract: Abstract. The present study was designed to evaluate the expression and subcellular distribution of the familial acute myelogenous leukemia-related factor (FAMLF). A 14-amino acid epitope of the predicted open reading frame of the FAMLF gene was identified using bioinformatics. This polypeptide was synthesized, conjugated to keyhole limpet hemocyanin and was subsequently used to produce antibodies. The antibody titer and specificity were characterized using ELISA and western blot assays, respectively. The anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that FAMLF was highly expressed in acute myeloid leukemia and BL patients, NB4 acute promyelocytic leukemia cells, U937 macrophage-like cells, K562 myeloid leukemia cells, U266 myeloma cells, HL60 promyelocytic cells, CA46 lymphoma cells, and especially in Raji BL cells, while low expression was observed in unaffected individuals. FAMLF may be involved in hematopoietic neoplasms by promoting cell proliferation and preventing cell differentiation (6,7). …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that FAMLF was highly expressed in acute myeloid leukemia and BL patients, NB4 acute promyelocytic leukemia cells, U937 macrophage-like cells, K562 myeloid leukemia cells, U266 myeloma cells, HL60 promyelocytic cells, CA46 lymphoma cells, and especially in Raji BL cells, while low expression was observed in unaffected individuals. FAMLF may be involved in hematopoietic neoplasms by promoting cell proliferation and preventing cell differentiation (6,7). …”
Section: Introductionmentioning
confidence: 99%
“…Using bioinformatics, we revealed the existence of at least three splice variants of FAMLF , named as FAMLF-1 , FAMLF-2 and FAMLF-3 , and also found miR181a1/b1 embedded in the second intronic regions of FAMLF gene family (see Figure 1 ). Furthermore, we were able to detect a doublet at 8 kDa by Western blot analysis of total protein lysate from AML patient's cell and AML cell lines [ 13 ]. The expression of FAMLF-1 was significantly higher in de novo adult AML than the control.…”
Section: Introductionmentioning
confidence: 99%